Super-Fast Sodium Storage Properties of Nitrogen-Doped Graphene-Based Material Synthesized via Arc-Discharge Method - Injun Jeon; Chunghun Kim; Minseung Kang; Hyun Woo Kim; Hong Chen; Hye Seon Youn; Myung Jong Kim; Chae-Ryong Cho (Batteries)
We investigated the electrochemical performance of undoped artificial graphene-based material (UAG) and N-doped graphene-based material (NAG, ~3.5% nitrogen doping), synthesized by the arc-discharge method, for sodium-ion battery anodes. The NAG demonstrated slightly superior fast-charging capability compared to UAG, achieving a specific capacity of 46.8 mAh g−1 at 30 A g−1, compared to UAG’s capacity of 36.7 mAh g−1, representing an enhancement of approximately 28%. It also showed high cycle stability, retaining a capacity of 100 mAh g−1 (retention ratio ~99.9%) after 2500 cycles at 5 A g−1, compared to UAG’s retention of 90 mAh g−1 (retention ratio ~95%). The diffusion behavior of the UAG and NAG samples was significantly higher than that of graphite. The improvement in electrochemical properties is attributed to the successful doping of nitrogen in NAG, which results in enhanced electrical conductivity and structural disordering.